2006
DOI: 10.1177/1074248406288761
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Administration of Abciximab During Percutaneous Coronary Interventions: Should This Be the Routine and Preferred Approach?

Abstract: The authors have had experience with administering abciximab as an intracoronary bolus in 96 high-risk patients undergoing percutaneous coronary interventions, specifically in situations in which there was anticipation of a high embolic load from thrombus/plaque burden at the site of the culprit lesion, saphenous vein graft culprit lesion, threatened abrupt closure, developing slow-flow, or no-reflow phenomena with distal embolization. Our uncontrolled data basically substantiate the safety of intracoronary ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…TIMI grade 3 flow). 26 Our findings revealed that no reflow and slow flow were effectively reduced and TIMI flow and MBG had better outcomes with IC injection of tirofiban. These results were in concordance with recent studies that proved that IC 27 and intralesional delivery of tirofiban through an aspiration catheter had better myocardial perfusion and fewer complications, even in complex PCI.…”
Section: Discussionsupporting
confidence: 51%
“…TIMI grade 3 flow). 26 Our findings revealed that no reflow and slow flow were effectively reduced and TIMI flow and MBG had better outcomes with IC injection of tirofiban. These results were in concordance with recent studies that proved that IC 27 and intralesional delivery of tirofiban through an aspiration catheter had better myocardial perfusion and fewer complications, even in complex PCI.…”
Section: Discussionsupporting
confidence: 51%
“…Compared with IV delivery of tirofiban, a higher drug concentration should result from IC delivery, leading to a greater procedural success rate (e.g., TIMI grade 3 flow) [36,37]. The most important effect is that a high local concentration of GPI has a thrombolytic effect, which improves TIMI flow [23,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Nitroglycerin was not been found to be effective (46). Other reports suggested efficacy of papaverine (47), nitroprusside (48,49), nicardipine (50), and abciximab (51). At present, there are no data from randomized trials showing the clinical benefit of these therapies.…”
Section: Prevention and Treatment Of Mvo And No-reflow: Experimental mentioning
confidence: 93%